A new species of Sphaerotheca Günther, 1859 (Anura: Dicroglossidae) from the degraded urban ecosystems of Bengaluru, Deccan Plateau, India - Deepak, P.; Dinesh, K.p.; Ohler, Annemarie; Shanker, Kartik; Channakeshavamurthy, B.h.; Ashadevi, J.s. (Zootaxa, 2020)
The dicroglossid genus Sphaerotheca was erected by Günther in 1859, with its range of distribution in South Asia. Since then, 13 species have been described and 10 species are considered valid. Many of these descriptions were from low to mid-elevation ranges of homestead areas, agroecosystems and degraded landscapes with a few from forested areas. In the present account, a new species of Sphaerotheca, a genetically distinct lineage with a morphological character set distinguishable from its congeners, is described from the surroundings of Bengaluru city, India. Based on evidence for the origin of the original specimen, we also designated a neotype for Rana variegata Gravenhorst, 1829, a junior primary homonym of Rana variegata Linnaeus, 1758, and permanently invalid name, so that it is now a subjective synonym of Rana (Tomopterna) breviceps rolandae Dubois, 1983.